Vùng tai biến trượt lở khu vực Mường Lay - Dũng, Nguyễn Chí; Nghinh, Lê Thị; Pha, Phan Đông; Lâm, Doãn Đình; Hưng, Nguyễn Quang; Hương, Nguyễn Thị Thanh (Vietnam Journal of Earth Sciences, 2018)
The landslide hazard’s zoning in Muong Lay